Unlocking design strategies for oxygen evolution reaction catalysts: Insights from a kinetic perspective via constrained ab initio molecular dynamics simulations - Shin, Dongyup; Han, Sang Soo (Elsevier BV, 2025)
To enhance the catalytic properties of prototypical iridium oxide (IrOx) for the oxygen evolution reaction (OER), we propose a novel approach that overcomes the limitations inherent in conventional density functional theory (DFT). By employing constant Fermi-level ab initio molecular dynamics simulations combined with slow-growth kinetic analysis, we explore the underlying factors influencing the catalytic activity of IrOx in the OER process. Our comprehensive examination revealed the pivotal roles played by the oxygen 2p orbital, Ir-O bond strength, and proton affinity in governing the efficacy of both the lattice oxygen mechanism (LOM) and the adsorbate evolution mechanism (AEM). This elucidation not only clarifies the complex relationships between the elemental factors and the catalytic activity but also provides a programmable strategy for catalyst design. This strategy is validated by a catalyst, E-IrTaO2 (lattice-elongated Ir-Ta bimetallic oxide), aimed at enhancing LOM selectivity for circumventing the scaling relationship. Notably, the LOM barrier in E-IrTaO2 is estimated to be about 0.2 eV lower than its AEM barrier, thereby strongly favoring the LOM pathway. This study signifies a notable departure from traditional DFT approaches, providing a new strategy for the rational design of high-performance OER catalysts based on a profound understanding of their operational fundamentals.